2002
DOI: 10.1590/s1135-57272002000500014
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de situación y propuestas de mejora en enfermería de atención primaria de Mallorca: un estudio con grupos focales

Abstract: Fundamento. La reforma de la atención primaria (RAP) ha dado lugar a mejoras importantes en la profesión enfermera. Objetivos del estudio: analizar los logros obtenidos por las enfermeras, identificar los problemas que tienen actualmente en atención primaria y proponer líneas de trabajo para el futuro. Método: Investigación cualitativa (técnica del grupo focal). Se realizaron ocho grupos segmentados según la categoría profesional y el puesto desempeñado. Dimensiones de análisis: rol de la enfermera, oferta y o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Despite this position has few rewards, it is generally accepted by nurses with a high degree of professional development [47]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this position has few rewards, it is generally accepted by nurses with a high degree of professional development [47]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, references are made to the health system working badly, by creating new positions and responsibilities for PHC without providing the parallel means to put them into practice, thus creating bad feeling between professionals and increasing stress [56,57]. Besides, Sancho-Viudes et al (2002) in the PHC environment in Mallorca identified - as problems to be solved - the poor adequacy of staff dimension compared to the population to be cared for, the need for updating clinical guides and protocols, the lack of specific training in community nursing, and the subsequent need for a specialization in community nursing [47]. Kramer and Schmalenberg (2008), when they describe the requirements that must be met in order to generate a good climate in the work place, point out the perception of staff adequacy [55].…”
Section: Discussionmentioning
confidence: 99%